Enhancing the gender-responsiveness of your project's technical farmer training events - Farnworth, Cathy Rozel; Badstue, Lone B. (International Maize and Wheat Improvement Center, 2017)
This resource sets out simple suggestions for ensuring that women as well as men feel included in training events, are fully informed about technological options, learn effectively, and have the confidence to implement what they have learned. Over time, if their experience has been successful, they should be able to build on the training course to innovate by themselves in response to their needs and changes in the wider environment.